Gugatan Verstek: Menimbang Hak Tergugat Dan Efisiensi Proses Beracara - Adzaky Luthfi Radiant; Sidi Ahyar Wiraguna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Default judgments (verstek) are commonly applied in Indonesian civil proceedings to address court backlogs, yet they risk violating defendants' procedural rights due to ineffective summons verification under HIR Articles 126-129. This study aims to analyze how verstek potentially breaches audi alteram partem and due process principles while identifying normative gaps enabling plaintiff abuse. Employing a juridical-normative approach with library research, the population comprises civil procedure regulations (HIR, Rv, UU No. 48/2009), Supreme Court decisions, and recent literature (2021-2025); purposive sampling selects relevant primary and secondary legal materials. The researcher serves as the key instrument, utilizing doctrinal, grammatical, systematic, and thematic analysis techniques. Findings reveal ambiguities in